IMPLEMENTASI AKTIVITAS FISIK OLAHRAGA JALAN KAKI MENGONTROL KADAR GULA DARAH PADA KELUARGA DENGAN DIABETES MELLITUS: STUDI LITERATUR - Yuli Astuti (Yayasan Pendidikan Medika Indonesia, 2021)
Diabetes Mellitus is a metabolic disorder characterized by increased blood sugar levels that can cause damage to various systems of the human body. This literature study aims to examine the effects, methods and results of physical activity walking on controlling blood sugar in people with diabetes mellitus. This study uses a literature study, articles are obtained from 1 database, namely Google Scholar using inclusion and exclusion criteria. The keyword used in this literature search is “Diabetes Mellitus. Blood Sugar Levels. Walking” and “Diabetes Mellitus. Blood Glucose. Walking